#TITLE_ALTERNATIVE# - (NIM 20107009), EFENDI
The growth of Aedes sp population was assumed depended on the fluctuation of water availability in habitat that influenced by the daily rainfall and the geometric shape of habitat. The maturation and hatching of surviving eggs and the mortality or larva were depended on the fluctuation of water availability in habitat. Firstly, Aedes sp population model was constructed based on five growth stage (immature egg, mature egg, larvae, nulliparous and parous female). The dynamics of Aedes sp population was described by projection population matrix. The entries of matrix projection population were probability of transition and fecundity of female Aedes sp.